The beats : a teaching companion - Grace, Nancy McCampbell (Beat studies series., 2021)
"This volume addresses the integration of Beat authors, texts, and themes into formal academic settings. Addressed to secondary and post secondary instructors, the book features six domains: 1) Foundational Issues, 2) Beat Literary Genres, 3) Beat Literary Topics, 4) Beat Lineages and Legacies, 5) Selected Resources, and 6) Sample Assignments"--